Pengaruh Family Functioning dan Emotional Regulation terhadap Romantic Beliefs pada Anak Perempuan Pertama - Adinda Fajarwati; Zulian Fikry (MAN 4 Kota Pekanbaru, 2026)
This research was conducted to analyze the effect of family functioning and emotional regulation on romantic beliefs among firstborn daughters. An approach using quantitative methods with purposive sampling was employed. The study involved 217 firstborn daughters who met the predetermined eligibility requirements. Information was gathered through the Family Assessment Device (FAD), the Emotion Regulation Questionnaire (ERQ), and the Romantic Beliefs Scale (RBS), and were statistically examined through multivariable regression analysis. The findings demonstrated that familial dynamics and emotional regulation simultaneously exerted a substantial influence on romantic beliefs (F = 239.500, p < .001), explaining 69.1% of the variance (R² = .691). Furthermore, both variables had a positive and significant effect on romantic beliefs, with emotional regulation demonstrating a stronger contribution than family functioning. These findings suggest that healthy family functioning and effective emotional regulation play important roles in shaping romantic beliefs among firstborn daughters.